INFLUENCE OF RECOGNITION ON EMPLOYEE JOB PERFORMANCE IN AVIATION INDUSTRY, TANZANIA - Chindengwike, James (Journal Business Administration: Entrepreneurship and Creative Industry, 2025)
The study attempted to examine the influence of recognition on employee job performance in aviation Industry, Tanzania. The population of study comprised of employees of Tanzania Airports Authority (TAA), where, the sample size was 152. The study used a case study design and employed both quantitative and qualitative approaches. Data from employee who have no administrative roles were collected using questionnaire, while interviews were used to collect data from employees who hold administrative positions. Qualitative data were analyzed using descriptive statistics and Structuring Model, whereby; qualitative data were analyzed using Content Analysis. The study observed that recognition with respect to policy, forms and frequency influences employee performance Tanzania Airports Authority. Thus, the study recommends that, the management of TAA should take deliberate measures to performance of employees.